Predictive and Diagnostic Values of Systemic Inflammatory Indices in Bronchopulmonary Dysplasia - Linxia Cao; Xiangye Liu; Tingting Sun; Yuan Zhang; Tianping Bao; Huaiping Cheng; Zhaofang Tian (MDPI AG, 2023)
Background: Bronchopulmonary dysplasia (BPD) is the most common respiratory complication in preterm infants, and there is a lag in the diagnosis of BPD. Inflammation is a vital pathogenic factor for BPD; we aim to evaluate the predictive and diagnostic values of systemic inflammatory indices in BPD. Methods: Between 1 January 2019 and 31 May 2023, the clinical data of 122 premature infants with a gestational age of <32 weeks in the Department of Neonatology, the Affiliated Huai'an No. 1 People's Hospital of Nanjing Medical University, were retrospectively collected and classified into non-BPD (n = 72) and BPD (n = 50) groups based on the National Institute of Child Health and Human Development 2018 criteria. To compare the general characteristics of each group, we identified the independent risk variables for BPD using multivariate logistic regression analysis, compared the systemic inflammatory indices at birth, 72 h, 1 week, 2 weeks, and 36 weeks postmenstrual age (PMA), and constructed the receiver operating characteristic curves of neutrophil-to-lymphocyte ratio (NLR) diagnosis of BPD at different time points. Results: ① The independent risk factors for BPD in preterm infants were birth weight, small for gestational age, and days of oxygen therapy (all p < 0.05). ② At 72 h and 1 week after birth, the serum NLR of the BPD group was higher than for the non-BPD group (p < 0.05). Furthermore, the neutrophil count (N), NLR, monocyte-to-lymphocyte ratio (MLR), systemic immune-inflammation index, systemic inflammation response index (SIRI), and pan-immune-inflammation value of infants with BPD were higher than the non-BPD group at 3 weeks after birth (p < 0.05). Moreover, at 36 weeks of PMA, the serum N, NLR, MLR, and SIRI of BPD infants were higher than those of non-BPD infants (p < 0.05). ③ The NLR of infants with and without BPD gradually increased after birth, reaching a peak at 72 h and 1 week, respectively. At 3 weeks postnatal, the NLR had the highest predictive power for BPD, with an area under the curve (AUC) of 0.717 (p < 0.001); the sensitivity was 56% and specificity was 86.1%. In addition, the NLR at 36 weeks of PMA exhibited some diagnostic value for BPD. The AUC was 0.693 (p < 0.001), the sensitivity was 54%, and specificity was 83.3%. Conclusions: At 3 weeks after birth and 36 weeks of PMA, some systemic inflammation indices (like N, NLR, SIRI) of preterm infants with BPD have specific predictive and diagnostic values; these indices may help the management of high-risk preterm infants with BPD.